Concurrent validity and reliability of sprinting force-velocity profile assessed with GPS devices in elite athletes - Clavel, P.; Leduc, C.; Morin, J.-B.; Owen, C.; Samozino, P.; Peeters, A.; Buchheit, M.; Lacome, M. (International Journal of Sports Physiology and Performance, 2022)
Purpose: The aims of this study were to (1) assess the concurrent validity of global positioning systems (GPSs) against a radar device to measure sprinting force-velocity (F-v) profiles and (2) evaluate the interunit reliability of 10-Hz GPS devices (Vector S7, Catapult Innovations).